(untitled) (Al-Academy, 2019)
The emergence of artistic movements in Western countries was after the period of modernity. They have introduced a great dialectical problem at the level of thought and discourse, which necessitated a change in the course of the aesthetic discourse into new visions. Thus, the present research aims to identify the aesthetic discourse of pop artists’ Art and its representations in the outputs of the students of the Department of Art Education. The theoretical framework included two sections: the first one, what is the aesthetic discourse and the second is the educational bases of the students’ outputs. The procedures of the current research included the analytical descriptive approach. The research sample consisted of (4) outputs chosen according to the intended method from the fourth your students in the department of Art Education in the College of Fine Arts /University of Baghdad. As for the results of the research, it has become clear from the analysis of the samples that it approached the aesthetic discourse of Bob Art, which is based on multiple indications and undermining the center and heading towards the open ends following Andy Warhol and his work in terms of repetition and the use of radiant colors, and that the representation took a retrospective form with some change. The researcher concluded that the representation occurs through the conjunction of the form and the content according to characteristics closer to the simulation, or through the adoption of formal and technical characteristics with the change of the content, because of the impact of the intellectual and cultural structure of the community.